NAMANGANLÍ QARAQALPAQLAR - Prekeeva, A. (SCIENCE and SOCIETY, 2023)
This article is devoted to the history, customs and traditions, language issues of the Karakalpaks living outside of Karakalpakstan, in the Minbulak district of Namangan region.